Electoral reform and the behavioural personalisation of voters: the impact of system change on the importance of party leader and party evaluations in New Zealand elections. (4th May 2018) - Liu, Imogen T.
ABSTRACT: This paper investigates the effect of a change in electoral system on the relative importance of party leader versus party evaluations in the case of New Zealand national elections, in which an electoral reform from a majoritarian to a mixed system was instituted in 1996. Prior literature on the personalisation of politics suggests that differences in electoral system can affect the importance of party leader and party evaluations in voting choice whereby majoritarian systems exhibit stronger leader effects and mixed systems weaker effects. At the same time, more proportional systems are theorised to enhance party leader visibility and their consequent importance in voting choice. Drawing data from the New Zealand Election Study, the results provide partial support for the moderating effect of system change on the increasing importance of leader evaluations and decreasing importance of party evaluations. The introduction of MMP visibly reduces the importance of party evaluations, but the increasing importance of leader evaluations is to some extent independent of reform.